Kajian Faktor-Faktor Yang Mempengaruhi Pendapatan Pelaku Usaha di Kawasan Wisata Kota Lama Semarang - Arimianto Prakosa; Muhammad Muktiali (Teknik PWK (Perencanaan Wilayah Kota), 2016)
The Semarang Old City’s tourism area is one of the resorts owned by the city of Semarang. This tourism area has great potential to be developed. As the times goes by, the tourism area of Semarang City’s evolved. It can be seen from the presence of tourists or visitors and business actors in the Semarang Old City’s area. With the participation of stakeholders, such as government, private, and businessmen in the tourism area of Semarang Old City can thrive in the economic sector, either the regional economy or local economy, or business actors. In this study, one thing to be observed is the influence of the Semarang Old City tourism area’s presence to the business actors’ economy.The Semarang Old City set as heritage tourist area, with all its uniqueness. In the past, the Semarang Old City’s tourist area was not as busy as now. Lately, the tourist area of Semarang Old City has developed; it can be seen from the number of visitors every day. In addition, it can be seen that many trade sectors and services come up in the Semarang Old City’s area. Therefore, this study aimed to determine the characteristics relationship of  business activity with business actors’ income in the Semarang Old City’s tourist area.The aims of this study were to examine and analyze the relationship between the business activity’s characteristic with business actors in the Semarang Old City’s tourism area. These objectives can be achieved by determining the goals, which were reviewing the characteristics of the area, visitors, business activities, entrepreneurs, and analyzing the influence of the Semarang Old City tourism area’s presence to the business actors’ economy. The analysis method used in this research is quantitative and descriptive methods with analysis technique that is supported by the data obtained through the observation and questionnaires.Based on this research, it is known the factors that influence the income of business actors in the Semarang Old City’s tourism area, which are buyers’ busy time, the amount of labor, business activity duration per day and the duration of business activities per week.